Partisipasi Politik Masyarakat Dalam Sistem Noken Pemilihan Legislatif Tahun 2019 Kecamatan Mbua Kabupaten Nduga - Elopere, Samuel; Pati, Agustinus B.; Liando, Daud M. (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study is how is the political participation of the community in the Noken System for the 2019 Legislative Elections in Nduga Regency, in particular the Mbua District. The research was conducted for 2 (two) months, from February to March 2022 at the Mbua District Office. This research uses a descriptive method with a qualitative approach. Data obtained from primary data and secondary data through observation, interviews, and literature or documentary studies. The focus of this research is the political participation of the people in the tradition of the 2019 legislative election noken system, Mbua District, Nduga Regency. Based on the conclusions of this study, it is a challenge in itself that the Nduga Regency has just been formed so that the membership is still new and of course inexperienced in the political world, which means very little experience as active participation in elections.